Early outcomes from the CLASP IID trial roll‐in cohort for prohibitive risk patients with degenerative mitral regurgitation. Issue 4 (18th May 2021) - Lim, D. Scott; Smith, Robert L.; Zahr, Firas; Dhoble, Abhijeet; Laham, Roger; Lazkani, Mohamad; Kodali, Susheel; Kliger, Chad; Hermiller, James; Vora, Amit; Sarembock, Ian J.; Gray, William; et al.
Abstract: Objectives: We report the 30‐day outcomes from the roll‐in cohort of the CLASP IID trial, representing the first procedures performed by each site. Background: The currently enrolling CLASP IID/IIF pivotal trial is a multicenter, prospective, randomized trial assessing the safety and effectiveness of the PASCAL transcatheter valve repair system in patients with clinically significant MR. The trial allows for up to three roll‐in patients per site. Methods: Eligibility criteria were: DMR ≥3+, prohibitive surgical risk, and deemed suitable for transcatheter repair by the local heart team. Trial oversight included a central screening committee and echocardiographic core laboratory. The primary safety endpoint was a 30‐day composite MAE: cardiovascular mortality, stroke, myocardial infarction (MI), new need for renal replacement therapy, severe bleeding, and non‐elective mitral valve re‐intervention, adjudicated by an independent clinical events committee. Thirty‐day echocardiographic, functional, and quality of life outcomes were assessed. Results: A total of 45 roll‐in patients with mean age of 83 years and 69% in NYHA class III/IV were treated. Successful implantation was achieved in 100%. The 30‐day composite MAE rate was 8.9% including one cardiovascular death (2.2%) due to severe bleeding from a hemorrhagic stroke, one MI, and no need for re‐intervention. MR≤1+ was achieved in 73% and ≤2+ in 98% of patients. 89% of patients were in NYHA class I/II ( p  < .001) with improvements in 6MWD (30 m; p  = .054) and KCCQ (17 points; p  < .001). Conclusions: Early results representing sites with first experience with the PASCAL repair system showed favorable 30‐day outcomes in patients with DMR≥3+ at prohibitive surgical risk.